2015
DOI: 10.1155/2015/412607
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Vertebral Augmentation with Polyethylene Mesh and Allograft Bone for Traumatic Thoracolumbar Fractures

Abstract: Purpose. In cases of traumatic thoracolumbar fractures, percutaneous vertebral augmentation can be used in addition to posterior stabilisation. The use of an augmentation technique with a bone-filled polyethylene mesh as a stand-alone treatment for traumatic vertebral fractures has not yet been investigated. Methods. In this retrospective study, 17 patients with acute type A3.1 fractures of the thoracic or lumbar spine underwent stand-alone augmentation with mesh and allograft bone and were followed up for one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The other studies were prospective or retrospective cohort studies. The posterior (PO (n = 75)17-77, PP (n = 39) ( Fan et al, 2017 ; Kocis et al, 2020 ; Lee et al, 2013 ; Lyu et al, 2016 ; Pishnamaz et al, 2015 ; Vanek et al, 2014 ; Wang et al, 2017 ; Wang et al, 2013 ; Zhang et al, 2016 ; Zou et al, 2017 ; Afzal et al, 2008 ; Altay et al, 2007 ; Andress et al, 2002 ; Butt et al, 2007 ; Caruso et al, 2019 ; Caruso et al, 2018 ; Ding et al, 2021 ; He et al, 2013 ; Jiang et al, 2020 ; Kerschbaumer et al, 2019 ; Korovessis et al, 2008b ; Korovessis et al, 2017 ; Korovessis et al, 2014 ; Li et al, 2016b ; Manson et al, 2020 ; Padalkar and Mehta, 2017 ; Podet et al, 2020 ; Proietti et al, 2014 ; Sanli et al, 2019 ; Shao et al, 2020 ; Shin et al, 2020 ; Teyssedou et al, 2012 ; Trungu et al, 2019 ), SA (n = 13)) ( He et al, 2013 ; Kerschbaumer et al, 2019 ; Teyssedou et al, 2012 ; Costa et al, 2009 ; Grelat et al, 2018 ; Hartmann et al, 2012 ; Hartmann et al, 2015 ; Klezl et al, 2011 ; Maestretti et al, 2014 ; Saget et al, 2014 ; Schmelzer-Schmied et al, 2009 ; Schulz et al, 2015 ), and anterior (AO (n = 5)) ( Wood et al, 2005 ; Shin et al, 2020 ; Liang et al, 2017 ; Oskouian et al, 2006 ; Smith et al, 2010 ; Yang et al, 2012 ) approaches seemed to be the most often reported surgical techniques. As an anterior scopic technique only thoracoscopy was reported, in the found studies it was not used as the sole surgical technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other studies were prospective or retrospective cohort studies. The posterior (PO (n = 75)17-77, PP (n = 39) ( Fan et al, 2017 ; Kocis et al, 2020 ; Lee et al, 2013 ; Lyu et al, 2016 ; Pishnamaz et al, 2015 ; Vanek et al, 2014 ; Wang et al, 2017 ; Wang et al, 2013 ; Zhang et al, 2016 ; Zou et al, 2017 ; Afzal et al, 2008 ; Altay et al, 2007 ; Andress et al, 2002 ; Butt et al, 2007 ; Caruso et al, 2019 ; Caruso et al, 2018 ; Ding et al, 2021 ; He et al, 2013 ; Jiang et al, 2020 ; Kerschbaumer et al, 2019 ; Korovessis et al, 2008b ; Korovessis et al, 2017 ; Korovessis et al, 2014 ; Li et al, 2016b ; Manson et al, 2020 ; Padalkar and Mehta, 2017 ; Podet et al, 2020 ; Proietti et al, 2014 ; Sanli et al, 2019 ; Shao et al, 2020 ; Shin et al, 2020 ; Teyssedou et al, 2012 ; Trungu et al, 2019 ), SA (n = 13)) ( He et al, 2013 ; Kerschbaumer et al, 2019 ; Teyssedou et al, 2012 ; Costa et al, 2009 ; Grelat et al, 2018 ; Hartmann et al, 2012 ; Hartmann et al, 2015 ; Klezl et al, 2011 ; Maestretti et al, 2014 ; Saget et al, 2014 ; Schmelzer-Schmied et al, 2009 ; Schulz et al, 2015 ), and anterior (AO (n = 5)) ( Wood et al, 2005 ; Shin et al, 2020 ; Liang et al, 2017 ; Oskouian et al, 2006 ; Smith et al, 2010 ; Yang et al, 2012 ) approaches seemed to be the most often reported surgical techniques. As an anterior scopic technique only thoracoscopy was reported, in the found studies it was not used as the sole surgical technique.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, only data of neurological intact patients that sustained a type A fracture was available. Advantages of the SA procedures include its minimal invasive approach, restoration of kyphosis, maintaining kyphosis correction and early pain reduction ( He et al, 2013 ; Kerschbaumer et al, 2019 ; Teyssedou et al, 2012 ; Costa et al, 2009 ; Grelat et al, 2018 ; Hartmann et al, 2012 ; Hartmann et al, 2015 ; Klezl et al, 2011 ; Maestretti et al, 2014 ; Saget et al, 2014 ; Schmelzer-Schmied et al, 2009 ; Schulz et al, 2015 ; Verlaan et al, 2005 ). This procedure is mainly compared to conservative treatment with a brace, or a combination of posterior fixation and vertebroplasty or kyphoplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Other attempts have been made to design a specialized percutaneous bone graft delivery and containment system (Optimesh ® , Spineology, Inc., St. Paul, MN) that stimulates ingrowth of new bone (21). Large studies demonstrating the outcomes for this technology still need to be performed to demonstrate efficacy in kyphosis correction or protection (28). However, some data suggests that non-operative treatment in young neurologically intact patients with mild traumatic compression fractures may result in worse disability outcomes at long-term follow-up despite following TLICS guidelines (29).…”
Section: Percutaneous Vertebral Augmentationmentioning
confidence: 99%